1993
DOI: 10.1111/j.1467-6427.1993.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Informal polygamy’: a suitable case for treatment?

Abstract: The authors describe an atypical family structure which they term ‘informal polygamy’ and give two examples from their therapeutic practice. They go on to outline a number of dilemmas in helping such families, including whether such a family structure is more usefully viewed as transitional or stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…D'Hondt and Vandewiele (1980) reported that the majority of secondary school students in their study were against polygamy. Thus, in studies of both Arab and African cultures, polygamy has been shown to affect the women and their children emotionally, and to create an atmosphere of competition between both co‐wives and children (Oyefeso & Adegoke, 1992; Rivett & Street, 1993).…”
Section: Polygamymentioning
confidence: 99%
See 1 more Smart Citation
“…D'Hondt and Vandewiele (1980) reported that the majority of secondary school students in their study were against polygamy. Thus, in studies of both Arab and African cultures, polygamy has been shown to affect the women and their children emotionally, and to create an atmosphere of competition between both co‐wives and children (Oyefeso & Adegoke, 1992; Rivett & Street, 1993).…”
Section: Polygamymentioning
confidence: 99%
“…Despite widespread academic interest in polygamy (see Altman, 1993; Chaleby, 1985, 1987; Chamie, 1986; El‐Islam, 1975; Haggi, 1974; Makanjuola, 1987; Topouzis, 1985; Welch & Block, 1981), relatively little research addresses family therapy among polygamous families in general and in Arab society in particular. Indeed, the closest published findings are on therapeutic dilemmas treating “informal polygamy” in a monogamous, Western society (Rivett & Street, 1993). The following study therefore contributes to a small but growing body of research differentiating skills needed for work with Arab‐Muslim families (Abdal‐Ati, 1974; Al‐Krenawi, Maoz, & Riecher, 1994; El‐Islam, 1983, 1989; Lipson & Meleis, 1983; Savaya, 1995; Weisfeld, 1990).…”
mentioning
confidence: 99%
“…It has also been used synonymously with polygyny, there are several forms of polygamy: polyandry refers to the marriage of one woman to two or more husbands, polygyndry is a situation in which two or more women are at the same time married to two or more men, and polygynandry is used to refer to group marriage (Al-Krenawi and Graham 2009). The other type of polygamy is an informal polygamy which describes relationships characterized by the simultaneous existence of a legal marriage of one man to a woman and an affair with a second woman that has become a stable feature of the family structure (Rivett and Street 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As seen in some regions in other countries, polygamy is a common condition, particularly rural villagers in southeastern region of Turkey. Some husbands were preferred to polygamy due to the various factors including the high economic level, infertility of their wife, religious beliefs, cultural factors, desire to increase the number of children, particularly sons or satisfaction of sexual desires, also existent psychiatric or medical disease of wifes 17,18,23 . Polygamy, in both high and low income households has negative consequences, for all family members.…”
Section: Discussionmentioning
confidence: 99%